Value Intertwining: Need Translation, Solution Calibration, and Mutual Reinforcement in AI-Powered Digital Commerce-Cybersecurity Collaboration (2025-2026) - Ba, Ju (International Journal of Multidisciplinary Research, 2026)
Artificial intelligence (AI) has enabled deep value intertwining between digital commerce and cybersecurity, operating through an interactive loop: need translation (AI decodes implicit, cross-domain needs that stakeholders cannot articulate independently), solution calibration (AI tailors tools to embed both commercial and security values), and mutual reinforcement (calibrated solutions amplify each domain’s core value while creating new intertwined value). This review synthesizes 5 key studies (2025-2026) to unpack the intertwining logic: AI translates SMBs’ implicit need for "accessible security" and commerce’s unspoken demand for "non-disruptive protection" into actionable cybersecurity requirements; calibrates modular architectures, PETs, and multi-agent systems to balance inclusivity, privacy, and risk mitigation; and reinforces commercial growth via trusted experiences and security relevance via practical deployment. Findings reveal that: value intertwining is driven by AI’s ability to bridge "need ambiguity" and "value conflict"; modularity and interpretability are critical for solution calibration; intertwined value (e.g., trust-driven conversion, relevance-driven security adoption) is the most sustainable outcome. This framework offers a value-centric, interactive perspective on cross-domain collaboration, guiding stakeholders to build systems where commerce and security are not just complementary but inherently interdependent.